Faktor-faktor yang memengaruhi penduduk lanjut usia berobat jalan di Provinsi Jawa Timur - Irdam Ahmad; Ayu Lailal Barikha (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
This study aims to determine factors influencing outpatient treatment of elderly population in East Java Province. The analysis used raw data of the 2017 National Socio-Economic Survey (Susenas) conducted by Statistics Indonesia. The unit of analysis is population aged 60 years and over, with a total sample of 6,511 persons. Multilevel binary logistic regression model was employed for the analysis. The results showed that nearly half (49.6%) of the unwell elderly population did not seek treatment. The reasons for this behaviour include they did not have enough money (especially in rural areas), chose to self-medicate, and felt no need for treatment. For the elderly who seek outpatient treatment, the most visited health facility is doctor or midwife practice. The results also show that factors affecting the behavior of elderly population in outpatient treatment are economic status, working status, activity disruption, and health insurance ownership.